2014
DOI: 10.1097/mlr.0000000000000169
|View full text |Cite
|
Sign up to set email alerts
|

Safety Organizing, Emotional Exhaustion, and Turnover in Hospital Nursing Units

Abstract: Safety organizing is beneficial to caregivers in multiple ways, especially on nursing units with high levels of adverse events and over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 61 publications
0
33
0
3
Order By: Relevance
“…There are some valuable and instructive exceptions though. For instance, analysing the impact of "mindful organising" across three large hospitals, Vogus, Cooil, Sitterding, and Everett (2014) calculated that this generated a 13.6% decrease in turnover, representing an average hospital saving of between $169,000 and $1,014,560. Such analyses will be very valuable in terms of generating organisational buy-in to the potential of mindfulness, thus helping facilitate research going forward that can enable the promise of the research reviewed here to be substantiated (see Edwards et al (2015) for recommendations on conducting such analyses).…”
Section: Discussionmentioning
confidence: 99%
“…There are some valuable and instructive exceptions though. For instance, analysing the impact of "mindful organising" across three large hospitals, Vogus, Cooil, Sitterding, and Everett (2014) calculated that this generated a 13.6% decrease in turnover, representing an average hospital saving of between $169,000 and $1,014,560. Such analyses will be very valuable in terms of generating organisational buy-in to the potential of mindfulness, thus helping facilitate research going forward that can enable the promise of the research reviewed here to be substantiated (see Edwards et al (2015) for recommendations on conducting such analyses).…”
Section: Discussionmentioning
confidence: 99%
“…There have also been some HRO research with respect to space (Schulman, 2008); energy (Hoffmann et al, 1995;Miller, 2009;Hopkins, 2009;Lekka & Sugden, 2011); education (Stringfield, 1995;Taylor & Angelle, 2000;Azzaro, 2005;Bellamy et al, 2005;Stringfield et al, 2008); food retail (Ciravenga & Brenes, 2016); Information technology ( Valorinta, 2009;Carlo et al, 2012) and virtual organisations (Grabowski & Roberts, 2016). Some have aimed at the relationship with other concepts such as resilience engineering (Aven & Krohn, 2014;Righi et al, 2015;Bergstrom et al, 2015;Haavik et al, 2016;Harvey et al, 2016;Le Coze, 2016) and safety (Vogus & Sutcliffe, 2007a;Vogus & Sutcliffe, 2007b;Ausserhofer et al, 2013;Vogus et al, 2014;Vogus & Iacobucci, 2016). There is no evidence of a research conducted across different types of organisations at the same time to test the theory, demonstrate how it could be progressively achieved.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Aikens et al (2014) conducted a cost-benefit analysis based on rates of self-reported burnout, concluding that the findings were suggestive of a 20% increase in worker productivity, potentially representing employer savings of up to $22,580 per employee year. Equally striking was an analysis of intensive care units across three large hospitals by Vogus, Cooil, Sitterding, and Everett (2014), who calculated that the impact of engaging in 'mindful organising' was a 13.6% decrease in turnover, representing an average hospital saving of between $169,000 and $1,014,560. Such analyses will be useful going forward in terms of generating managerial and organisational 'buy in' to the potential value of mindfulness, thus helping facilitate the further research that is needed to fully substantiate the promise of the research reviewed here.…”
Section: Future Directionsmentioning
confidence: 99%